L3 Effects on serum bile acids, pruritus, and safety with up to 72 weeks of odevixibat treatment: pooled data from the PEDFIC 1 and PEDFIC 2 studies in children with progressive familial intrahepatic cholestasis. (12th September 2022) - Loomes, Kathleen M; Verkade, Henkjan J; Thompson, Richard J; Kamath, Binita M; Hardikar, Winita; Lacaille, Florence; Mozer-Glassberg, Yael; Shteyer, Eyal; Calvo, Pier Luigi; Dalgic, Buket; Grammatikopoulos, Tassos; Rajwal, Sanjay R; et al.
Abstract : Introduction/Background: Progressive familial intrahepatic cholestasis (PFIC) is a group of rare paediatric cholestatic liver diseases. In the phase 3 PEDFIC 1 and PEDFIC 2 studies, the efficacy and safety of odevixibat, an ileal bile acid transporter inhibitor, were examined in patients with PFIC. Aim: Using pooled data from PEDFIC 1 and PEDFIC 2, we analysed changes in serum bile acids (sBAs) and pruritus and examined the safety profile of odevixibat in patients treated for up to 72 weeks, comparing those who responded to odevixibat treatment (Rs) with nonresponders (NRs). Subjects and Methods: PEDFIC 1 was a 24-week, randomised, placebo-controlled study, and PEDFIC 2 is an ongoing 72 week extension study. This pooled, exploratory analysis spans from patients' first dose of odevixibat to a data cut-off date of 4 December 2020. Patient pruritus was rated using the Albireo observer-reported outcome (ObsRO) instrument. Treatment Rs met either sBA response criteria (defined per the PEDFIC 1 study protocol; table 1) or sBA and/or pruritus response criteria (table 1). Safety assessments included evaluation of treatment-emergent adverse events (TEAEs). Results: Overall, 84 patients received odevixibat (mean age, 5.0 years; median odevixibat exposure, 53 weeks). During weeks 0−72, 30/81 (37%) patients were sBA Rs and 49/84 (58%) patients were sBA and/or pruritus Rs. Mean changes in sBA levels from baseline to the last assessment in this analysis period, weeks 70−72, were –230 and −117 µmol/L in sBA Rs and NRs, respectively. From baseline to the last assessment interval in this analysis period, weeks 61−72, sBA Rs and NRs had mean changes in pruritus score of –2.2 and –0.9, respectively. Additional changes over time in sBAs and pruritus scores in patients meeting either criteria for treatment response are shown in the table 1. TEAEs were reported in 87% and 86% of sBA Rs and NRs, respectively, and in 86% and 83% of sBA and/or pruritus Rs and NRs. Two sBA Rs and 2 NRs (or 3 sBA and/or pruritus Rs and 2 NRs) had TEAEs leading to discontinuation. Summary and Conclusion: Patients with PFIC who responded to odevixibat (based on protocol-defined response criteria) had sustained improvements in mean sBAs and pruritus scores over time. sBA Rs had larger improvements in pruritus than sBA NRs; pruritus improvements in those who did not meet sBA R criteria may reflect either perceived treatment effects or patients with a partial sBA R. Odevixibat treatment was generally well tolerated in both Rs and NRs.